Targeting Mitochondrial ROS-Mediated Ferroptosis by Quercetin Alleviates High-Fat Diet-Induced Hepatic Lipotoxicity - Jiang, Jin-Jin; Zhang, Guo-Fu; Zheng, Jia-Yi; Sun, Ji-Hu; Ding, Shi-Bin (Frontiers in Pharmacology, 2022)
Background: The protective effect of quercetin on nonalcoholic fatty liver disease (NAFLD) has been reported, but its mechanism remains poorly understood. Recently, quercetin was reported to be capable of inhibiting ferroptosis, which is a recognized type of regulated cell death. Moreover, hepatic ferroptosis plays an important role in the progression of NAFLD, but experimental evidence is limited. Hence, our study aimed to investigate the effect of quercetin on hepatic ferroptosis in high-fat diet (HFD)-induced NAFLD and further elucidate the underlying molecular mechanism. Methods: C57BL/6 mice were fed either a normal diet (ND), an HFD, or an HFD supplemented with quercetin for 12 weeks. Hepatic lipid peroxidation, steatosis, ferroptosis and iron overload were examined. In vitro, steatotic L-02 cells was used to study the potential mechanism. Results: We found that the HFD caused lipid peroxidation, lipid accumulation and ferroptosis in the liver, which were rescued by quercetin supplementation. Consistent with the in vivo results, quercetin alleviated lipid droplet accumulation and reduced the levels of lipid reactive oxygen species (ROS) and ferroptosis in steatotic L-02 cells. Using a mitochondrial ROS (MtROS) scavenger (Mito-TEMPO) and ferroptosis speciﬁc inhibitor (Fer-1), we found that quercetin remarkably alleviated lipid droplet accumulation and lipid peroxidation by reducing MtROS-mediated ferroptosis in steatotic L-02 cells. Conclusion: Our data showed that HFD consumption induced lipid accumulation and triggered ferroptosis in liver, ultimately leading to hepatic lipotoxicity, which can be alleviated by quercetin. Findings from this study provide new insight into the mechanism by which quercetin can be used for the prevention and treatment of NAFLD.